2015
DOI: 10.1053/j.gastro.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations in Colorectal Cancer: Emerging Biomarkers

Abstract: Colorectal cancer (CRC) is a leading cause of cancer deaths worldwide. One of the fundamental processes driving the initiation and progression of CRC is the accumulation of a variety of genetic and epigenetic changes in colon epithelial cells. Over the past decade, major advances have been made in our understanding of cancer epigenetics, particularly regarding aberrant DNA methylation, microRNA (miRNA) and noncoding RNA deregulation, and alterations in histone modification states. Assessment of the colon cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
518
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(529 citation statements)
references
References 339 publications
(241 reference statements)
2
518
0
9
Order By: Relevance
“…1 The carcinogenesis of colorectum is driven by genetic and epigenetic alterations and also closely regulated by tumour-host interactions. 2,3 Accumulating evidence has revealed immune microenvironment could help tumor cells to evade immune destruction by the infiltrating immune cells. 4 Immunotherapy, especially checkpoint antibodies targeting the PDCD1 (programmed cell death 1, PD-1) and B7-H1 (programmed death-ligand 1 (PD-L1)) protein, has been emerged as a promising strategy to treat a number of cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…1 The carcinogenesis of colorectum is driven by genetic and epigenetic alterations and also closely regulated by tumour-host interactions. 2,3 Accumulating evidence has revealed immune microenvironment could help tumor cells to evade immune destruction by the infiltrating immune cells. 4 Immunotherapy, especially checkpoint antibodies targeting the PDCD1 (programmed cell death 1, PD-1) and B7-H1 (programmed death-ligand 1 (PD-L1)) protein, has been emerged as a promising strategy to treat a number of cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Few such studies have reported speciic variations among the mutations observed in chromosomal instability and microsatellite instability tumors. Most of the microsatellite instability tumors have 30% more mutations in β-catenin when compared to Adenomatous polyposis coli protein (APC), while β-catenin mutations are exceptionally rare in nonmicrosatellite instability cancers [40]. This is an indirect conirmation recommending that the microsatellite instability occurs prior to the inactivation of the Adenomatous polyposis coli protein Adenomatous polyposis coli protein (APC) pathway.…”
Section: Genomic Instabilitymentioning
confidence: 97%
“…[30][31][32] Colorectal cancer represents a heterogeneous group of neoplasms resulting from genomic and epigenomic alterations, which influence and are influenced by tumor-host interactions. [33][34][35][36] A strong immune response to colorectal cancer manifested as high density of CD3 C , CD8…”
Section: Introductionmentioning
confidence: 99%